Lost - Cast, P. C; Cast, Kristin (Cast, P. C. House of night, other world., 2018)
Zoey worries about her brother using Old Magick while he is in his world, so she and her friends travel to an alternative version of the House of Night, where dangers take the form of friends and allies are found in strange places.